Bethany-Hillside, Clay County - Richmeier, Alexandra (Kansas State University, The Chapman Center for Rural Studies, 2010)
Mabel Dunham did much to preserve the history of Bethany Church while an active member. Her personal memoirs and weekly column in the Clay Center Times newspaper bring to life the love and devotion the community felt for their small rural Kansas church and insight to the people who lived in the area.
Alexandra Richmeier, “Bethany-Hillside, Clay County,” Chapman Center Research Collections, accessed October 14, 2020, https://ccrsresearchcollections.omeka.net/items/show/36.
Keywords: Bethany-Hillside Congregation; Broughton Methodist Church; Clay County; Countryside United Methodist Church; Leonardville; Milford Dam